Combination of bioactive phytochemicals and synthetic anthelmintics: In vivo and in vitro assessment of the albendazole-thymol association - Miro, Maria Victoria (2020)
The search of novel strategies for anthelmintic control is a crucial need considering the widespread increase in resistant parasitic populations in livestock. Bioactive phytochemicals may contribute to improve parasite control by enhancing the effect of existing anthelmintic drugs. The aim of the current work was to evaluate the in vivo and in vitro pharmaco-chemical interaction and the in vivo efficacy of the combination of albendazole (ABZ) with thymol (TML) in lambs naturally infected with resistant gastrointestinal nematodes. Thirty (30) lambs were allocated into three experimental groups. Each group was treated orally with either ABZ (5 mg/kg), TML (150 mg/kg, twice every 24 h) or the co-administration of both compounds. Blood samples were collected between 0 and 51 h post-treatment and TML, ABZ and its metabolites were measured by HPLC. Individual faecal samples were collected at days -1 and 14 post-treatment to perform the faecal egg count reduction test. Additionally, the effect of TML on the sulphoreduction and sulphonation of ABZ sulphoxide was assessed in vitro using ruminal content and liver microsomes, respectively. The metabolism of TML in the ruminal content was very low and the monoterpene exhibited a low degree of association with the particulate phase of the ruminal content. No changes in the pharmacokinetic behavior of ABZ sulphoxide were observed in the presence of the natural product (TML). In contrast, the ABZ sulphone Cmax and AUC were lower (P 0.002 and 0.001 respectively) in the co-administered animals (0.16 ± 0.07 μg/mL and 3.63 ± 1.21 μg.h/mL) compared with those that received ABZ alone (0.45 ± 0.15 μg/mL and 9.50 ± 2.84 μg.h/mL). TML was detected in the bloodstream between 1 and 48 h post-treatment, which indicates the time of target nematodes being exposed to the bioactive monoterpene. However, the in vivo efficacy of TML was 0% and the presence of this terpene did not increase the efficacy of ABZ. The presence of TML significantly inhibited the ruminal sulphoreduction (P 0.001) and the hepatic sulphonation (P 0.001) of ABZ sulphoxide. These observations point out that in vivo pharmaco-parasitological studies are relevant to corroborate the adverse kinetic/metabolic interactions and the efficacy of bioactive natural products combined with synthetic anthelmintics.